A retrospective review of Granulomatous Interstitial Nephritis (GIN) amongst HIV-infected patients at Groote Schuur Hospital, Cape Town - Nel, Debbie (University of Cape Town, 2015)
Includes bibliographical references. === Introduction: High numbers of granulomata have been identified on kidney biopsy at Groote Schuur Hospital in HIV positive patients. In the literature granulomatous interstitial nephritis (GIN) is most commonly attributed to sarcoid and drug reactions and occurs in 0.5- 1.37% of kidney biopsies. Current data is only from developed countries and rarely in HIV positive individuals. As our yield of GIN appeared high we retrospectively reviewed the established HIV database of kidney biopsies to establish the likely causes of this histological finding in our HIV positive population. An extensive literature review was also performed with the intention of developing a diagnostic, and therapeutic, algorithm applicable to GIN in a South African setting. Subjects and Methods: A database of 370 HIV positive kidney biopsies dating from January 2005 was retrospectively reviewed. All patients with GIN on kidney biopsy were analysed. Medication history, creatinine, urine protein/creatinine ratio, CD4 count and serological evidence of vasculitis were recorded. A radiological evaluation and search for positive TB cultures was performed. Patients were divided according to the likely aetiology of GIN, ranging from least to most likely TB-GIN, together with the likelihood of a druginduced or ascending infection-related aetiology. Mortality data was obtained from reviewing the Clinicom system and patient records. Ethics was granted from the UCT ethics committee. Results: 45 patients (12.2%) had evidence of (GIN). 26 (57.8%) were female. Median age was 33 years (IQR 29-37). TB-GIN was likely in 62.2% of patients .Median CD4 was 126 cells/mm3 (IQR 54-237). There were 6 cases of possible paradoxical TB IRIS identified. [median CD4 count of 74 cells/mm3 (IQR 36-170)]. 49% of patients were on a drug implicated in GIN, with 11% on >1 drug [The most common drug being cotrimoxazole]. 6 patients had evidence of ascending infection. No patients had vasculitis.14/45 (31%) patients died on follow up with a median time to death of 119 days (IQR 30-444 days). Interpretation: GIN is common in our HIV population. TB is the most likely cause however other aetiologies require consideration, especially drugs. TB IRIS should be considered if cART has been recently initiated and the CD4 count is low. A proposed diagnostic algorithm was developed as part of this study, together with treatment guidelines. Further research is needed to evaluate the utility of these in a clinical setting.